Interrelation of intrinsic defects and optical absorption properties of lithium niobate (LiNbO3) crystals - Ngurah Made, D. P. (World Scientific Publishing, 2005)
The optical absorption of pure lithium niobate (LiNbO3) single crystals were measured from the ultraviolet to the visible range with the incident light being parallel to the z axis of the crystals. The wavelength dependence of the absorption coefficient α and its root α1/2 (α versus hν and α1/2 versus hν, respectively) were calculated and the characteristics of the absorption edges were discussed. The absorption edges below 3.6 eV of all samples are attributable to indirect transition. The energy gap Eg and E′g of the crystals, which correspond to the direct transition and the indirect transition, respectively, and the energy of phonons Ep taking part in the indirect transition were calculated. It was found that the energy band structure depends on [Li]/[Nb] ratio of lithium niobate crystals. The change of E′g may be attributable to the distortion of energy band structures resulting from the intrinsic defects.